Insights Into the Detection Selectivity of Redox and Non-redox Based Probes for the Superoxide Anion Using Coumarin and Chromone as the Fluorophores - Wang, Yuchen; Jia, Shumi; Yu, Zhenyan; Wen, Hui; Cui, Huaqing (Frontiers in Chemistry, 2021)
In this study we evaluated the applicability of various superoxide anion sensors, which were designed based on either redox or non-redox mechanisms. Firstly, both redox and non-redox based superoxide anion probes were designed and synthesised using either coumarin or chromone as the fluorophores, and the photophysical properties of these probes were measured. Subsequently, the sensing preference of both types of probes towards various ROS were evaluated. We found non-redox based O2•- probes exhibited broad sensing ability toward various ROS. In contrast, redox based O2•- probes showed clear reactivity hierarchy which was well correlated to the oxidizing strength of the ROS. Lastly, the detection selectivity of redox based O2•- recognising probes were also observed when balancing various factors, such as reaction transformation rate and reactant ROS concentrations. Herein, we concluded the selectivity advantage of redox based O2•- probes.